2023
DOI: 10.3390/ijms24043316
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for Early Detection, Prognosis, and Therapeutics of Esophageal Cancers

Abstract: Esophageal cancer (EC) is the deadliest cancer worldwide, with a 92% annual mortality rate per incidence. Esophageal squamous cell carcinoma (ESCC) and esophageal adenocarcinoma (EAC) are the two major types of ECs, with EAC having one of the worst prognoses in oncology. Limited screening techniques and a lack of molecular analysis of diseased tissues have led to late-stage presentation and very low survival durations. The five-year survival rate of EC is less than 20%. Thus, early diagnosis of EC may prolong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 128 publications
(125 reference statements)
0
8
0
Order By: Relevance
“…And they have different geographic patterns, causes and prognosis [12]. Patients with cancers have poor prognosis mostly because of the late-stage at diagnosis [13,14]. So it is very important to nd the valuable diagnostic marker for combating cancers.…”
Section: Discussionmentioning
confidence: 99%
“…And they have different geographic patterns, causes and prognosis [12]. Patients with cancers have poor prognosis mostly because of the late-stage at diagnosis [13,14]. So it is very important to nd the valuable diagnostic marker for combating cancers.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in China over a 24-year period revealed that ESCC constituted around 95% of esophageal cancer cases in the country, whereas the incidence of EAC was relatively low. However, due to rapid economic growth and the adoption of more Westernized diets and lifestyles, the occurrence of EAC has been increasing annually in both urban and rural areas of China (Rai et al, 2023;Luo et al, 2021;Liang et al, 2017). This trend necessitates the attention of researchers in cancer prevention and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…China has the highest number of patients with esophageal cancer globally, with ESCC being the predominant subtype, responsible for over 90% of deaths, resulting in 193,000 annual fatalities nationwide (Lin et al, 2017). ESCC is the primary histological type of esophageal cancer, accounting for approximately 90% of all cases, and it is highly prevalent in Asia, Africa, and South America (Rai et al, 2023). The abnormal growth of the esophageal squamous epithelium serves as a signi cant precancerous lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal endoscopic biopsy combined with histological analysis is widely regarded as the most reliable method for early detection and diagnosis. Advanced endoscopic imaging techniques, such as chromoendoscopy, virtual chromoendoscopy, and magnifying endoscopy, can significantly enhance the sensitivity of detecting early-stage cancer[ 14 ]. Minimally invasive endoscope-guided treatment offers effective management for the majority of ESCCs and precancerous lesions, leading to a 90% chance of survival for up to 5 years[ 15 ].…”
Section: Introductionmentioning
confidence: 99%